LIX1L aggravates MASH-HCC progression by reprogramming of hepatic metabolism and microenvironment via CD36 - Leng, Yingrong; Zhang, Yanqiu; Cheng, Yang; Ye, Shengtao; Zheng, Ying; He, Mengmeng; Wu, Enyi; Kong, Lingyi; Zhang, Hao (Pharmacological research, 2025)
Limb expression 1-like protein (LIX1L) is an essential player in liver disorders, but its function in metabolic dysfunction-associated steatohepatitis (MASH) and associated hepatocellular carcinoma (HCC) progression remains obscure. Here, we identify LIX1L as a key integrative regulator linking lipid metabolism and inflammation, adipose tissue and hepatic microenvironment, which promotes MASH progression. LIX1L significantly upregulates in MASH patients, mouse models, and palmitic acid-stimulated hepatocytes. Lix1l deletion inhibits hepatic lipid accumulation, inflammation, and fibrosis as well as adipocyte differentiation by downregulating CD36, alleviating MASH and associated HCC progression in mice. Mechanistically, metabolic stress promotes PARP1-mediated poly-ADP-ribosylation of LIX1L to increase stability and RNA binding ability of LIX1L. Subsequently, LIX1L binds to AU-rich element in the 3’UTR and CDS of CD36 mRNA, thus mitigating CD36 mRNA decay. Furthermore, LIX1L deficiency-mediated downregulation of CD36 reprograms the tumor-prone liver microenvironment with increased cytotoxic T lymphocytes and reduced immunosuppressive cell proportions. These data indicate a systematic function of LIX1L in the pathogenesis of MASH and underscore targeting PARP1/LIX1L/CD36 axis as a feasible strategy for treatment of MASH and associated HCC. [Display omitted] •LIX1L expression is upregulated in the liver of MASLD patients, mice, and cell models.•LIX1L knockout mitigated, while LIX1L overexpression promoted the development of MASH and HCC.•Metabolic stress promotes PARP1-mediated LIX1L PARylation, increasing the stability and RNA binding ability of LIX1L.•LIX1L stabilize CD36 mRNA to regulate adipocyte differentiation and lipid metabolism.•LIX1L-CD36 axis remodels immune landscape in MASH and associated HCC microenvironment.